Antenatal Sonographic Diagnosis of a Case of Alobar Holoprosencephaly (Anwer Khan Modern Medical College Journal, 2018)
Holoprosencephaly, a disorder resulting from failure of cleavage or incomplete differentiation of the forebrain structures at various levels or to various degrees, is related to hereditary factors, chromosomal anomalies, cytogenetic abnormalities, and environmental teratogenic factors. This anomaly is resulted from the failure of diverticulation and cleavage of primitive prosencephalon during weeks 4-8 of gestation. In this study, we described a case of HPE in a neonate with gestational age of 35 weeks.Anwer Khan Modern Medical College Journal Vol. 9, No. 1: Jan 2018, P 68-70